2019
DOI: 10.1002/anie.201906790
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ubiquitin‐Based Probe for Metalloprotease Deubiquitinases

Abstract: Deubiquitinases (DUBs) are a family of enzymes that regulate the ubiquitin signaling cascade by removing ubiquitin from specific proteins in response to distinct signals. DUBs that belong to the metalloprotease family (metalloDUBs) contain Zn2+ in their active sites and are an integral part of distinct cellular protein complexes. Little is known about these enzymes because of the lack of specific probes. Described here is a Ub‐based probe that contains a ubiquitin moiety modified at its C‐terminus with a Zn2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…In addition to the chelators described above, a number of thiol‐based compounds have also been investigated as MBL inhibitors, including captopril, bisthiazolidines, and various thiol carboxylates [15–17] . Recent reports describing 8‐thioquinoline (8‐TQ) as a potent zinc binding motif also prompted us to investigate its capacity to inhibit MBLs [18–20] . Although we were able to show that 8‐TQ is a potent zinc binder with the capacity to inhibit MBLs, we also found that it has the tendency to rapidly oxidize to the corresponding disulfide, eliminating its zinc binding and MBL inhibiting properties.…”
Section: Introductionmentioning
confidence: 83%
“…In addition to the chelators described above, a number of thiol‐based compounds have also been investigated as MBL inhibitors, including captopril, bisthiazolidines, and various thiol carboxylates [15–17] . Recent reports describing 8‐thioquinoline (8‐TQ) as a potent zinc binding motif also prompted us to investigate its capacity to inhibit MBLs [18–20] . Although we were able to show that 8‐TQ is a potent zinc binder with the capacity to inhibit MBLs, we also found that it has the tendency to rapidly oxidize to the corresponding disulfide, eliminating its zinc binding and MBL inhibiting properties.…”
Section: Introductionmentioning
confidence: 83%
“…13e) with a zinc chelator 8-mercaptoquinoline (8-MQ) linked to the C terminus of Ub. 129 Inhibition assays showed that the probe can inhibit Rpn11/Rpn8 with an IC 50 value about 2 mM. When incubated with HeLa cell lysates, the probe captured metal-loDUBs POH1, AMSH, and AMSH-LP.…”
Section: This Journal Is © the Royal Society Of Chemistry 2020mentioning
confidence: 98%
“…More recent developments initiated by Huib and his team included breakthroughs in challenging areas such as the first molecular probes for ubiquitin E3 ligases (Mulder et al, 2016) as well as probes that can target metalloprotease DUBs (Hameed et al, 2019). The latter, which provides access to an interesting subset of the DUB enzyme family, has been attempted previously for many years.…”
Section: Major Contributions To the Ubiquitin And Chemical Biology Fieldmentioning
confidence: 99%
“…Novel metalloprotease probes(Hameed et al, 2019) [With permission-Figure 5A]. (A) Schematic representation of pull-down reagents used in the assay.…”
mentioning
confidence: 99%